Penetrating Micelle for Reversing Immunosuppression and Drug Resistance in Pancreatic Cancer Treatment. Issue 18 (13th March 2022) - Chen, Qinjun; Wang, Qingbing; Wang, Yu; Chu, Yongchao; Luo, Yifan; You, Haoyu; Su, Boyu; Li, Chao; Guo, Qin; Sun, Tao; Jiang, Chen
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is on of the most lethal malignant tumors with relatively poor prognosis, characterized with insufficient drug penetration, low immune response and obvious drug resistances. The therapeutic inefficiency is multifactorially related to its specific tumor microenvironment (TME), which is representatively featured as rich stroma and immunosuppression. In this work, a versatile drug delivery system is developed that can coencapsulate two prodrugs modified from gemcitabine (GEM) and a signal transducer and activator of transcription 3 (STAT3) inhibitor (HJC0152), and the gradient pH variation is further sensed in the TME of PDAC to achieve a higher penetration by reversing its surficial charges. The escorted prodrugs can release GEM intracellularly, and respond to the hypoxic condition to yield the parental STAT3 inhibitor HJC0152, respectively. By inhibiting STAT3, the tumor immunosuppression microenvironment can be re‐educated through the reversion of M2‐like tumor associated macrophages (M2‐TAMs), recruitment of cytotoxic T lymphocytes and downregulation of regulatory T cells (Treg s). Furthermore, cytidine deaminase (CDA) and α‐smooth muscle actin (α‐SMA) expression can be downregulated, plus the lipid modification of GEM, the drug resistance of GEM can be greatly relieved. Based on the above design, a synergetic therapeutic efficacy in PDAC treatment can be achieved to provide more opportunity for clinical applications. Abstract : In this work, a pancreatic ductal adenocarcinoma‐penetrating micelle is developed that can re‐educate the tumor immunosuppression microenvironment by inhibiting STAT3, and reverse gemcitabine resistance, serving for an efficient treatment.